2020
DOI: 10.1038/s41598-020-71932-9
|View full text |Cite
|
Sign up to set email alerts
|

Manure application increased crop yields by promoting nitrogen use efficiency in the soils of 40-year soybean-maize rotation

Abstract: It is great of importance to better understand the effects of the long-term fertilization on crop yields, soil properties and nitrogen (N) use efficiency in a rotation cropping cultivation system under the conditions of frequent soil disturbance. Therefore, a long-term field experiment of 40 years under soybean-maize rotation was performed in a brown soil to investigate the effects of inorganic and organic fertilizers on crop yields, soil properties and nitrogen use efficiency. Equal amounts of 15N-labelled ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…This 38 years fertilization experiment was established in 1979; the field soil properties and block design were described by Hua et al (2020) . The field experiment was conducted under a rotation of maize–maize–soybean.…”
Section: Methodsmentioning
confidence: 99%
“…This 38 years fertilization experiment was established in 1979; the field soil properties and block design were described by Hua et al (2020) . The field experiment was conducted under a rotation of maize–maize–soybean.…”
Section: Methodsmentioning
confidence: 99%
“…According to Jackson and Smith [103], while studying the effects of fertilizer application rate and time on grain yields, noted that animal manures are a potential source of N for cereal crops. Sradnick and Feller [104] established that commercially available organic fertilizers obtained from plant and animal sources generally contained a higher amount of N than P. Moreover, Hua et al [105] showed that animal manure application increased crop productivity enhancing N use efficiency in the soils of a 40-year soybean-maize rotation. Based on the above discussion, we also realize that agronomic efficiency of animal-derived fertilizers is highly dependent on its N availability.…”
Section: Dose Calculation and Yield Potential Assessmentmentioning
confidence: 99%
“…The reduction in GHGs caused by the production of biogas from abattoir waste was determined using the IPCC-developed mathematical computational method (B-sustain, 2013;Hua et al, 2020;JGCRI, 2018;Tolera and Alemu, 2020), demonstrated as GHG reduction potential of AD equivalent to the approximate of GHG emissions from dumpsites minus the approximate of GHG emissions from AD:…”
Section: Reduction Of Ghgs Using Biogas Technologymentioning
confidence: 99%